PENGARUH EPS, ROA, FIRM SIZE, DAN DER TERHADAP RETURN SAHAM - Bahrudin, Tasya Fauziah; Dicky Arisudhana (CV. Denasya Smart Publisher, 2025)
Stock Return is a key indicator for investors to evaluate the level of gain from stock investments. The return value can be influenced by various internal company factors, including financial ratios that reflect corporate performance. This study aims to analyze the effect of EPS, ROA, Firm Size, and DER on stock returns in food and beverages sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The research method used is a quantitative approach using multiple linear regression analysis processed using SPSS software version 19. The sample was selected using purposive sampling, involving 39 companies from a total population of 101 that met the established criteria. The results indicate that partially, EPS, ROA, and Firm Size do not have a significant effect on stock returns. Whereas DER do have a significant effect on stock returns partially.